Physicochemical Properties of Characterization of PVP/CA/AE Nanofiber - Pulungan, Meuretta Alawiyah; Sriyanti, Ida; Marlina, Leni (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2023)
Nanofibers are nanotechnologies with cross-sectional diameters ranging from tens to hundreds of nanometers. We explained the definition of nanofibers and their unique physicochemical characteristics. This study aimed to see the characterization of Polyvinyl pyrrolidone/Cellulose acetate/Aloe vera extract fiber. The fiber was made with a concentration of PVP/CA in 13% (w/w) and an Aloe vera extract in 10% (w/w) using the electrospinning method. The electrospinning technique involves an electrohydrodynamic process in which liquid polymer droplets are electrified to produce jets that elongate to produce fibers. Electrospinning is an easy, fast, and simple technique for producing fibers with sizes ranging from micrometers to nanometers. Process parameters used in this research, such as flow rate of 0,20 ml/hour, high voltage of 12 kV, and drum speed is 200 rpm with the distance to the needle tip of the collector is 75 cm. The result showed that fiber PVP/CA/AE morphology is bead free and homogeneous. The average diameter of PVP/CA/AE fibers was 1115 nm.These results indicate that the resulting fiber is in the form of nanofibers. A small fiber diameter will result in a broader surface area. The XRD result shows that the PVP/CA/AE fibers have a semi-crystal phase.